MMP-12, Secreted by Pro-Inflammatory Macrophages, Targets Endoglin in Human Macrophages and Endothelial Cells - Aristorena, Mikel; Gallardo-Vara, Eunate; Vicen, Matej; de Las Casas-Engel, Mateo; Ojeda-Fernandez, Luisa; Nieto, Concepción; Blanco, Francisco J; Valbuena-Diez, Ana C; Botella, Luisa M; Nachtigal, Petr; Corbi, Angel L; Colmenares, María; et al. (International journal of molecular sciences, 2019)
Upon inflammation, monocyte-derived macrophages (MΦ) infiltrate blood vessels to regulate several processes involved in vascular pathophysiology. However, little is known about the mediators involved. Macrophage polarization is crucial for a fast and efficient initial response (GM-MΦ) and a good resolution (M-MΦ) of the inflammatory process. The functional activity of polarized MΦ is exerted mainly through their secretome, which can target other cell types, including endothelial cells. Endoglin (CD105) is a cell surface receptor expressed by endothelial cells and MΦ that is markedly upregulated in inflammation and critically involved in angiogenesis. In addition, a soluble form of endoglin with anti-angiogenic activity has been described in inflammation-associated pathologies. The aim of this work was to identify components of the MΦ secretome involved in the shedding of soluble endoglin. We find that the GM-MΦ secretome contains metalloprotease 12 (MMP-12), a GM-MΦ specific marker that may account for the anti-angiogenic activity of the GM-MΦ secretome. Cell surface endoglin is present in both GM-MΦ and M-MΦ, but soluble endoglin is only detected in GM-MΦ culture supernatants. Moreover, MMP-12 is responsible for the shedding of soluble endoglin in vitro and in vivo by targeting membrane-bound endoglin in both MΦ and endothelial cells. These data demonstrate a direct correlation between GM-MΦ polarization, MMP-12, and soluble endoglin expression and function. By targeting endothelial cells, MMP-12 may represent a novel mediator involved in vascular homeostasis.
Keywords: monocytes; exprese genu; Humans; endoglin; Gene Expression; Endoglin; matrixová metaloproteinasa 12; Models, Biological; makrofágy; inflammation; Inflammation; lidé; zvířata; myši; Cells, Cultured; zánět; faktor stimulující granulocyto-makrofágové kolonie; Disease Susceptibility; náchylnost k nemoci; Mice; faktor stimulující kolonie makrofágů; Matrix Metalloproteinase 12; Endothelial Cells; Granulocyte-Macrophage Colony-Stimulating Factor; kultivované buňky; macrophages; Macrophage Colony-Stimulating Factor; MMP-12; biologické modely; endoteliální buňky; Animals; Macrophages; Inflammation Mediators; Disease Models, Animal; mediátory zánětu; modely nemocí na zvířatech; endothelial cells